1994
DOI: 10.1111/j.1365-2494.1994.tb02002.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro gas production kinetics of grass silages treated with different cell wall‐degrading enzymes

Abstract: Grass was treated with six different cell walldegrading enzymes and ensiled under different conditions [dry matter (DM) content, stage of maturity]. Silage samples were dried, ground and incubated with buffered rumen fluid. Gas production was monitored over 48 h and gas production curves were fitted to a modified Gompertz equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…45%) causes the effect of enzyme addition on fibre degradation and lactic acid production to diminish 31 . This could be because the silages originated from different swards with different harvesting dates and therefore also different harvesting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…45%) causes the effect of enzyme addition on fibre degradation and lactic acid production to diminish 31 . This could be because the silages originated from different swards with different harvesting dates and therefore also different harvesting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For silages made from these herbages it is important to use a technique that can record the degradation of soluble, as well as non‐soluble nutrients, such as by the use of the GP technique (e.g. Beuvink and Spoelstra, 1994; Cone et al. , 1999; Hetta et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 1997). Beuvink and Spoelstra (1994) showed that in vitro GP recordings could detect the effects of different ensiling treatments.…”
Section: Introductionmentioning
confidence: 99%
“…With automated in vitro GP recording systems, it is possible to analyse a large number of samples and to detect the degradation of soluble cell contents and non-soluble cell walls (Cone et al, 1997;Doane et al, 1997). Beuvink and Spoelstra (1994) showed that in vitro GP recordings could detect the effects of different ensiling treatments.…”
Section: Introductionmentioning
confidence: 99%